2013
DOI: 10.1128/mcb.00465-12
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 Paralog Complexes BCDX2 and CX3 Act at Different Stages in the BRCA1-BRCA2-Dependent Homologous Recombination Pathway

Abstract: The Rad51 paralogs are required for homologous recombination (HR) and the maintenance of genomic stability. The molecular mechanisms by which the five vertebrate Rad51 paralogs regulate HR and genomic integrity remain unclear. The Rad51 paralogs associate with one another in two distinct complexes: Rad51B-Rad51C-Rad51D-XRCC2 (BCDX2) and Rad51C-XRCC3 (CX3). We find that the BCDX2 and CX3 complexes act at different stages of the HR pathway. In response to DNA damage, the BCDX2 complex acts downstream of BRCA2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
178
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(200 citation statements)
references
References 41 publications
15
178
3
4
Order By: Relevance
“…Data to support this include binding of CX3 and BCDX2 ring structures to Holliday junctions and Holliday junction branch migration and resolution activities by these complexes in vitro (211,212). Evidence for BCDX2 acting upstream and CX3 downstream of RAD51 recruitment has been brought recently by RNA interference (RNAi) depletion studies (213).…”
Section: Homologous Recombinationmentioning
confidence: 90%
“…Data to support this include binding of CX3 and BCDX2 ring structures to Holliday junctions and Holliday junction branch migration and resolution activities by these complexes in vitro (211,212). Evidence for BCDX2 acting upstream and CX3 downstream of RAD51 recruitment has been brought recently by RNA interference (RNAi) depletion studies (213).…”
Section: Homologous Recombinationmentioning
confidence: 90%
“…7 RAD51D protein forms a complex with RAD51B, RAD51C and XRCC2 (BCDX2 complex), 8 which is responsible for RAD51 recruitment or stabilization at DNA damage sites. 9 Additionally, it has been described that RAD51D plays a role in telomere protection against attrition and chromosome fusion. 10 Loveday et al 6 identified inactivating mutations in RAD51D in eight of the 911 British cases with a familial history of BC/ OC (0.88%) and in one of the 1,060 British controls (0.09%).…”
Section: -5mentioning
confidence: 99%
“…Notably, RAD51 paralogs have been recently shown to participate in BRCA1/2-mediated HR (14,15). However, BRCA2 has been implicated in replication fork stabilization but not its restart (44,45).…”
mentioning
confidence: 99%